Cost-effectiveness of the faecal immunochemical test at a range of positivity thresholds compared with the guaiac faecal occult blood test in the NHS Bowel Cancer Screening Programme in England - Murphy, JFE; Halloran, SP; Gray, AM (BMJ Publishing Group, 2017)
Objectives Through the National Health Service Bowel Cancer Screening Programme (BCSP), men and women in England aged between 60 and 74 years are invited for colorectal cancer (CRC) screening every two years using the guaiac faecal occult blood test (gFOBT). The aim of this analysis was to estimate the cost-utility of the faecal immunochemical test (FIT) compared with gFOBT for a cohort beginning screening aged 60 at a range of FIT positivity thresholds. Design We constructed a cohort-based Markov state-transition model of CRC disease progression and screening. Screening uptake, detection, adverse event, mortality and cost data were taken from BCSP data and national sources, including a recent large pilot study of FIT screening in the BCSP. Results Our results suggest that FIT is cost-effective compared with gFOBT at all thresholds, resulting in cost savings and quality-adjusted life years gained over a lifetime time horizon. FIT was cost-saving (p<0.001) and resulted in QALY gains of 0.014 (95% CI: 0.012, 0.017) at the base case threshold of 180µg Hb/g faeces. Greater health gains and cost savings were achieved as the FIT threshold was decreased, due to savings in cancer management costs. However, at lower thresholds FIT was also associated with more colonoscopies (increasing from 32 additional colonoscopies per 1000 people invited for screening for FIT 180µg Hb/g faeces to 421 additional colonoscopies per 1000 people invited for screening for FIT 20µg Hb /g faeces over a 40-year time horizon). Parameter uncertainty had limited impact on the conclusions. Conclusions This is the first economic analysis of FIT screening in England using data directly comparing FIT with gFOBT in the NHS BSCP. These results for a cohort starting screening aged 60 suggest that FIT is highly cost-effective at all thresholds considered. Further modelling is needed to estimate economic outcomes for screening across all age cohorts simultaneously